Dissimilaridade genética e análise de trilha de cultivares de soja avaliada por meio de descritores quantitativos - Rigon, João Paulo Gonsiorkiewicz [UNESP]; Capuani, Silvia [UNESP]; Neto, José Félix de Brito; da Rosa, Genésio Mário; Wastowski, Arci Dirceu; Rigon, Carlos Alberto Gonsiorkiewicz (FapUNIFESP (SciELO), 2012)
In addition to the evaluations among genotypes, the use of multivariate techniques enables to restrict errors, mainly concerning genetic diversity, and therefore to predict combinations with greater heterotic effect, and the greater possibility of recovery of superior genotypes. The objective of this study was to evaluate the genetic divergence between 18 soybean cultivars based on six morphological characteristics. Path analysis was performed to verify the contribution of direct and indirect characters on grain yield. The Mahalanobis distance has founded techniques of both Tocher Method and dendrogram by Single Linkage. Five different groups were formed: with nine genotypes considered similar among them; while the cultivars CEP 59, Netuno and Urano formed groups isolated by the two grouping methods. The path analysis showed that the indirect characters had little influence on grain yield, with significant direct relationship with mass of 100 grain, and cultivars Tertulha and CEP 53 standing out with grain yields above 3.7 t.ha-1.
Genetic diversity and path analysis of soybeans cultivars evaluated by means of quantitative descriptors
Keywords: Genetic divergence.; Glycine max L. Merrill; Group; Glycine max